2023
DOI: 10.3390/geosciences13040103
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moisture Content on Subgrade Soils Resilient Modulus for Predicting Pavement Rutting

Abstract: The subgrade soil stiffness, which depends on the in-situ moisture content and soil index characteristics, is a key factor in pavement rutting. Due to variations in the compaction process used during construction and seasonal changes, the subgrade soil moisture content may deviate from the desired condition. The resilient modulus (MR), an important parameter of the Mechanistic-Empirical (M-E) pavement design process, is used to specify the subgrade soil stiffness. Repeated load triaxial tests, which can be cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…It is known from previous studies that M r values obtained from the cyclic triaxial test are in a lower interval than those obtained from the standard cyclic CBR test. In [16,21,23,33], the modulus values obtained from the cyclic triaxial test are in the intervals 20-90 MPa, 40-110 MPa, 55-80 MPa, and 56-159 MPa, respectively. All these results are fully comparable with the results in this paper.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known from previous studies that M r values obtained from the cyclic triaxial test are in a lower interval than those obtained from the standard cyclic CBR test. In [16,21,23,33], the modulus values obtained from the cyclic triaxial test are in the intervals 20-90 MPa, 40-110 MPa, 55-80 MPa, and 56-159 MPa, respectively. All these results are fully comparable with the results in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…The method has been tested and used by a number of authors [15,16,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Although the influence of the state of stress on the modulus has been correctly mentioned in some papers, and some studies have even been performed under an intuitively lower loading force not set up according to the standard CBR test [25,29], the question of the magnitude of the stress under the plunger has been overlooked.…”
Section: The Standard Cyclic Cbr Testmentioning
confidence: 99%
“…Predicting flexible pavement performance is highly dependent on the accuracy of the M R value. Islam and Gassman (2023) [28] found that the laboratory-measured M R obtained using the stress state in NCHRP-285 predicted higher rutting than the M R back calculated from FWD testing and PMED v2.6.2.2 default values. The rutting predicted from the laboratory-measured M R exceeded the field-measured distress but was below the design threshold.…”
Section: Introductionmentioning
confidence: 98%
“…The RLTT test is commonly used to measure the resilient modulus of subgrade soils in the laboratory [12][13][14][15][16][17][18]. This test is designed to simulate the stress induced by traffic loading through a series of cyclic deviator stresses applied to the specimen at different confining pressures [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, during actual service, precipitation infiltration and capillary rise may cause the subgrade moisture content to reach an equilibrium humidity higher than the optimal moisture content, leading to the degradation of subgrade support performance [5,6], further resulting in a decline in the pavement's service life. Rahman et al [7,8] revealed that specimens compacted at +2%w opt showed a lower modulus than specimens compacted at w opt . The soil moisture condition significantly influenced the subgrade modulus and the resulting subgrade rutting, which led to the severe degradation of road service performance.…”
Section: Introductionmentioning
confidence: 99%